Diversity of Fish Species Sold at Paccing Market, Awangpone District, Bone Regency Based on Morphological Identification - Tenri Gading, A. Nuraqilah; Darojat, Annisa Zakiyah (Indonesian Journal of Ecology and Conservation, 2026)
This study aimed to identify and describe the diversity of fish species sold at Paccing Market, Awangpone District, Bone Regency, through morphological identification. The research was conducted on June 26 and July 4 using a qualitative descriptive approach with purposive sampling techniques. Primary data were obtained through direct field observations, while secondary data were collected from relevant literature sources. The results revealed seven fish species originating from different aquatic habitats, including Chanos chanos, Oreochromis niloticus, Rastrelliger brachysoma, Mugil cephalus, Katsuwonus pelamis, Pennahia macrocephalus, and Sardinella gibbosa. Each species exhibits distinctive morphological characteristics as adaptations to its specific environment. These findings indicate that Paccing Market serves as a marketing site for diverse fish resources, reflecting the high potential for fish diversity in Bone Regency, which is supported by relatively stable oceanographic conditions and active community fishing practices. Therefore, sustainable management and utilization of these fisheries resources are essential to maintain ecological balance and economic continuity